DGCR8 is essential for tumor progression following PTEN loss in the prostate. (23rd July 2015) - Belair, Cassandra D; Paikari, Alireza; Moltzahn, Felix; Shenoy, Archana; Yau, Christina; Dall'Era, Marc; Simko, Jeff; Benz, Christopher; Blelloch, Robert
Abstract In human prostate cancer, the microRNA biogenesis machinery increases with prostate cancer progression. Here, we show that deletion of the Dgcr8 gene, a critical component of this complex, inhibits tumor progression in a Pten‐knockout mouse model of prostate cancer. Early stages of tumor development were unaffected, but progression to advanced prostatic intraepithelial neoplasia was severely inhibited. Dgcr8 loss blocked Pten null‐induced expansion of the basal‐like, but not luminal, cellular compartment. Furthermore, while late‐stage Pten knockout tumors exhibit decreased senescence‐associated beta‐galactosidase activity and increased proliferation, the simultaneous deletion of Dgcr8 blocked these changes resulting in levels similar to wild type. Sequencing of small RNAs in isolated epithelial cells uncovered numerous miRNA changes associated with PTEN loss. Consistent with a Pten–Dgcr8 association, analysis of a large cohort of human prostate tumors shows a strong correlation between Akt activation and increased Dgcr8 mRNA levels. Together, these findings uncover a critical role for microRNAs in enhancing proliferation and enabling the expansion of the basal cell compartment associated with tumor progression following Pten loss.